Gender Address Patterns in Banten Society - Evi Ratna Juwita (Journal of English Language Teaching and Cultural Studies, 2019)
The objectives of this study are to explore the common personal names used in Banten society based on the gender, to discuss the traditional titles used in Banten society in relation to gender, to explain the gender kinshipterms figures in Banten language, and to find out whether there is kind of gender address names is found at SMAN 3 Kota Serang. In this research, the researcher uses a qualitative research. The data are obtained from the informants. The informant in this research is Bantenese indigenous and the rural common people. The data for this study were collected by means of an interview and liearture review. The result of the research shows that those titles are still found among Banten society recently. The examples of names related to high social status are the previous Banten governor, Ratu Atut Chosiyah;and the current regent of Serang regency, Ratu Tatu Chasanah. Common people’s names related to Banten’s titles are also still exist. Moreover, names in connection with traditional title in Banten are used as names of streets in Banten.